Feasibility Study of Clinical Psychopragmatic from Philosophical Point of View in Student Creative Writing - Purwati Anggraini; Suyatno Suyatno; Tengsoe Tjahjono (Yayasan Adra Karima Hubbi, 2024)
Background. The issue in literary appreciation writing for UMM students of Indonesian Language Education needs an appropriate response. There are two causes Involved: technical and psychological Issues. Purpose. Despite adequate writing knowledge and skill, they experience challenges in writing literary appreciation. Method. Thus, it requires a comprehensive reconstruction of a new theory of clinical psycho-pragmatism, originating from psycholinguistics and clinical pragmatics, to address the issue. Results. The clinical psychopragmatic theory can be helpful as a research approach and potentially be the base of a new theory through knowledge reconstruction comprising ontologism, axiology, and epistemology. Conclusion. Thus, this theory, as a transdisciplinary theory, is more specific compared to a combination of psycholinguistics and clinical pragmatics.